2012
DOI: 10.1089/scd.2011.0150
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Human Bone Marrow-Derived Mesenchymal Stem Cells into Tendon Progenitor Cells by Ectopic Expression of Scleraxis

Abstract: Tendons and ligaments (T/L) are dense connective tissues of mesodermal origin. During embryonic development, the tendon-specific cells descend from a sub-set of mesenchymal progenitors condensed in the syndetome, a dorsolateral domain of the sclerotome. These cells are defined by the expression of the transcription factor scleraxis (Scx), which regulates tendon formation and several other characteristic genes, such as collagen type I, decorin, fibromodulin, and tenomodulin (Tnmd). In contrast to other mesenchy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
147
2
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(159 citation statements)
references
References 49 publications
8
147
2
2
Order By: Relevance
“…This might involve feedback regulation of Scx and Mkx expression through the tendon ECM, and recent studies have suggested that Dcn and Fmod are regulated by Mkx (Fig. 2B) (Ito et al, 2010;Liu et al, 2010;Alberton et al, 2012). These results point to a system by which the dynamics of fibril ultrastructure feedback on ECM production to modify tendon strength continuously.…”
Section: Ecm and Collagen Fibril Assembly During Tendon And Mtj Maturmentioning
confidence: 63%
See 2 more Smart Citations
“…This might involve feedback regulation of Scx and Mkx expression through the tendon ECM, and recent studies have suggested that Dcn and Fmod are regulated by Mkx (Fig. 2B) (Ito et al, 2010;Liu et al, 2010;Alberton et al, 2012). These results point to a system by which the dynamics of fibril ultrastructure feedback on ECM production to modify tendon strength continuously.…”
Section: Ecm and Collagen Fibril Assembly During Tendon And Mtj Maturmentioning
confidence: 63%
“…Scx is the earliest known marker of TPCs, and its overexpression transforms MSCs into tenocytes (Alberton et al, 2012), whereas Sox9 overexpression converts MSCs into cartilage ( Fig. 2A) (Takimoto et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…38 Ectopic expression of SCX in vitro has also been shown to induce the differentiation of MSCs into tendon progenitor cells. 39 Therefore, it is likely that SCX is expressed early in the differentiation of ESCs into tenocytes. Attempts were made to examine gene expression levels at 3 days, during the period of increased gel contraction in the presence of TGF-b3; however, the expression of all genes was low at this time point with large amounts of variability in their detection, which precluded getting any meaningful data.…”
Section: Figmentioning
confidence: 99%
“…In addition to the use of animal models to study tendon development, mesenchymal stem cells (MSCs) have been used to study tendon cell differentiation in vitro (15)(16)(17)(18). MSCs are multipotent progenitor cells that can be induced to differentiate into various tissues of mesodermal origin (19).…”
Section: Introductionmentioning
confidence: 99%